Religious-Contextual Integration of Pancasila Student Profile Values through Project-Based Learning (P5) in Islamic Religious Education at the Junior Secondary Level - Arief Syaifuddin; Nila Aulia; Ulfa Adilla; Angga Kurniawan; Dina Istiana (Jurnal Ilmu Sosial dan Humaniora, 2025)
Character-related competencies have become a central concern in Indonesian schooling under the Merdeka Curriculum, which mandates the Project for Strengthening the Pancasila Student Profile (P5) across school subjects. While prior research has examined P5 implementation in primary schools and in general subject areas, empirical evidence on how its values are embedded in Islamic Religious Education (PAI) at the junior secondary level remains limited, particularly with respect to the pedagogical mechanisms that translate spiritual content into character outcomes. This study examined how Pancasila Student Profile values are integrated through P5 in PAI learning at SMP Negeri 2 Jujuhan, a public junior secondary school in Bungo Regency, Indonesia. A qualitative descriptive design was applied, drawing on classroom observations across six PAI sessions and four P5 project sessions, semi-structured interviews with the principal, two PAI teachers, the P5 coordinator, and twelve students, and document analysis of teaching modules and school records. Data were analyzed through interactive analysis (data reduction, data display, and conclusion drawing), with source and method triangulation, member checking, and audit-trail maintenance used to verify trustworthiness. The findings indicate that integration occurs across three phases—planning, enactment, and evaluation—organized around four operative dimensions: faith and devotion, mutual cooperation, independence, and critical reasoning. The faith-and-devotion dimension was the most salient, while critical-reasoning competencies emerged more gradually and required intensive teacher scaffolding. Constraints centered on instructional time and uneven teacher readiness. The study contributes a religious-contextual integration model linking spiritual content with civic competencies, offering a structured pathway for character formation in Islamic education at the junior secondary level.